2019
DOI: 10.1111/nph.15807
|View full text |Cite
|
Sign up to set email alerts
|

Determining factors, regulation system, and domestication of anthocyanin biosynthesis in rice leaves

Abstract: Summary Wild and cultivated rice show a significant difference in anthocyanin biosynthesis in the leaf. The regulation system of anthocyanin biosynthesis in rice leaf and the causal mechanism of the difference in this biosynthesis between wild and cultivated rice remain largely unknown. In this study, a genome‐wide association study and transcriptome analysis were performed to identify the determinant factors and dissect the regulatory system for anthocyanin biosynthesis in rice leaves. OsC1, OsRb and OsDFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 50 publications
6
89
0
Order By: Relevance
“…It is interesting to note that Nipponbare, the rice cultivar used in this work, lacks OsC1 function, a R2R3-MYB gene necessary for OsCHS1 expression and anthocyanin production [43]. Thus, our seedlings do not accumulate anthocyanin even in B light, conditions where flavonoid production in cotyledons and leaves is enhanced in Arabidopsis or commonly seen in wild rice varieties [44].…”
Section: (C) Pigment Extraction and Quantificationmentioning
confidence: 91%
“…It is interesting to note that Nipponbare, the rice cultivar used in this work, lacks OsC1 function, a R2R3-MYB gene necessary for OsCHS1 expression and anthocyanin production [43]. Thus, our seedlings do not accumulate anthocyanin even in B light, conditions where flavonoid production in cotyledons and leaves is enhanced in Arabidopsis or commonly seen in wild rice varieties [44].…”
Section: (C) Pigment Extraction and Quantificationmentioning
confidence: 91%
“…Anthocyanin biosynthesis in different rice tissues is primarily controlled by R2R3-MYB transcription factors and the ternary MBW complexes, which comprised of R2R3-MYBs, bHLHs and WD40 [40,41]. In this study, the NIL- which was reported as a tissue regulator and controls pigmentation in hull [11].…”
Section: Discussionmentioning
confidence: 85%
“…The high anthocyanin content of many crops results from the increased expression of bHLH transcription factors [10]. WD40 is an ancient and highly conserved family of proteins that is involved in myriad plant cellular processes, such as transcriptional regulation, cell division, vesicle formation and transport, processing, signal transduction and so on [21].…”
Section: Introductionmentioning
confidence: 99%